Analysis of business process maturity and organisational performance relations = Analiza relacji pomiędzy dojrzałością procesową i wynikami organizacji - Kalinowski, Bartosz T. (Zielona Góra: Faculty of Economics and Management Press)
The paper aims to present results of the study on business process maturity in relation to organisational performance. A two-phase methodology, based on literature review and survey was used. The literature is a source of knowledge about business process maturity and organisational performance, whereas the research on process maturity vs organisational performance in Polish Enterprises provides findings based on 84 surveyed companies.
Keywords: dojrzałość procesowa; zarządzanie procesowe; wyniki organizacji; efektywność; process maturity; process management; organisational performance